Perancangan Sistem Informasi Forum Paud Berbasis WEB dengan Metode Waterfall - Fadly Ariadi; Dede Handayani; Khanif Faozi (JURIKOM (Jurnal Riset Komputer), 2022)
Early childhood education is highly valued by the Indonesian government because it is a coaching effort aimed at children from birth to the age of six that is carried out through the provision of educational stimuli to help physical and spiritual growth and development so that children are ready to enter further education. According to Ministry of Education and Culture data, South Tangerang City has 614 PAUD split among 7 sub-districts. To harmonize the implementation of education in PAUD, the Early Childhood Development Forum (PAUD) was formed which was legalized by law on April 21, 2021. Currently the PAUD Forum only has 200 members, There are still at least a few members because the socialization process has not been optimized because it only uses media messages with the Whatsapp application. Furthermore, the member registration process is still done manually, making it less efficient. The author will use the Waterfall method to design a web-based information system in this study. The findings of this study are hoped to transform the manual member registration process into a web-based computerized system. As a result, the registration process becomes faster and more efficient, and there is no need for an archiving location, which can affect the volume of the room, because all data is stored in the computer. In addition, the use of a web-based system will reduce errors that may occur due to user inaccuracies and also with this web-based system the socialization process about the existence of the PAUD Pembina Forum can be easily accessed by the public